Coherent polarization locking : an approach to mitigating optical damage in a pulsed Ho:YAG laser - Tan, L. H. (2013)
Intracavity optical damage is mitigated in a pulsed Ho:YAG laser cavity using the coherent polarization locking (CPL) technique. By splitting the available pump power into two individual Ho:YAG laser rods, we passively coherently locked two orthogonal polarization lasers with 9.13 mJ output pulse energies and 14 ns pulsewidths, and operating at 800 Hz repetition rate. A conventional Ho:YAG laser cavity with the same pump and cavity configuration results in severe optical damage when operating at <2 kHz repetition rate, thus limiting the output pulse energies to <5 mJ. We also demonstrated, to the best of our knowledge, the first pulsed operation within the entire CPL Ho:YAG laser cavity by Q-switching in one of the polarization arms, producing nanosecond pulses with no sign of pulse instability.